Analisis Hubungan Bilateral Indonesia dan Selandia Baru : Sinergi di Sektor Pariwisata, Transportasi dan Pembangunan Ekonomi - Zola Ari Setyanto; Selvia Sinurat; Grace Evelina Buji; Rinto Alexandro (FKIP, Universitas Palangka Raya, 2026)
This study analyzes the dynamics of Indonesia–New Zealand bilateral relations as developed through collaboration in tourism, air transportation, education, cultural diplomacy, and sustainable economic development. Employing a descriptive qualitative methodology, the study demonstrates that enhanced air connectivity (increased and more efficient flight links), technological integration at tourist destinations (use of digital tools and infrastructures to improve visitor experiences), and a mutual commitment to sustainable tourism (joint policies promoting environmental and community benefits) are critical in strengthening mobility and economic cooperation between the two states. In addition, the study finds that regional economic collaboration, Sister City programs, and cultural and educational interactions further reinforce long-term relations based on people-to-people connectivity. Cultural diplomacy, student exchanges, and strengthening the agribusiness sector provide direct benefits to communities. Overall, the study confirms that Indonesia–New Zealand relations are evolving into a strategic partnership that is inclusive, sustainable, and rich in potential for future cooperation